Decreased blood oxidative Stress after repeated muscle-damaging exercise - Nikolaidis, M. G.; Paschalis, V.; Giakas, G.; Fatouros, I. G.; Koutedakis, Y.; Kouretas, D.; Jamurtas, A. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To examine the effect of repeated muscle-damaging exercise on the time-course changes in several indices of muscle damage, and to compare them with changes in blood oxidative stress indices.